Computer-basiertes Training: ein neuer Weg der chirurgischen Aus- und Weiterbildung - Kallinowski, Friedrich; Mehrabi, Arianeb; Glückstein, Christina; Benner, Axel; Lindinger, Margit; Hashemi-Kalibar, Seyed-Bahram; Leven, Franz-Josef; Herfarth, Christian (Der Chirurg, 1997)
Computer-based training (CBT) programs teach the material of a specific field and at the same time offer various ways of objectively checking the knowledge gained. The interactive use of multimedia components, such as text, graphics, animation, sound, digital slide shows, videos and quizzes, facilitates the learning process. The aim of this study was the development and evaluation of a CBT program for use by surgeons teaching students. Using SuperCard, a teaching module for distal radius fracture (DRF) was developed, containing detailed clinical information. Video clips and vivid animation combine theoretical knowledge with practical experience. Fourth-year medical students (n = 103) were tested after using the module for 90 min. Other students (n = 47) served as the control group. In a 90-min lecture, DRF was discussed. In all evaluated criteria (distinctness, detailed description, presentation of materials, structure, motivation to learn, time saved while learning and memory retention), CBT gained 15-20 % better scores than the lecture. Although 87 % of the students stated that their experience with computers was limited or insufficient, 100 % found the use of CBT systems helpful in student teaching. Most of them suggested the use of such programs as a exam preparation/self study method (90 %) or as a supplement to a lecture (40 %). Based on these evaluations, it is clear that CBT modules are an appropriate future teaching and learning system that will be well accepted. In conclusion, CBT programs should be integrated into medical education as a valuable supplement. With this aim, CBT systems should be developed and used at universities as an information system for the surgical residency program.
Zusammenfassung in deutscher und englischer Sprache
Gesehen am 21.08.2025